2012
DOI: 10.1002/gps.3790
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of yogic meditation for family dementia caregivers with depressive symptoms: effects on mental health, cognition, and telomerase activity

Abstract: BACKGROUND This study examined the effects of brief daily yogic meditation on mental health, cognitive functioning, and immune cell telomerase activity in family dementia caregivers with mild depressive symptoms. METHODS Thirty-nine family dementia caregivers (mean age 60.3 years old (SD=10.2)) were randomized to practicing Kirtan Kriya or listening to relaxation music for 12 minutes per day for eight weeks. The severity of depressive symptoms, mental and cognitive functioning were assessed at baseline and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
281
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(297 citation statements)
references
References 47 publications
5
281
3
4
Order By: Relevance
“…Moreover, these findings might inform the development and delivery of interventions that aim to improve the cognitive well being of caregivers through targeting the psychological sequelae associated with the caregiving experience. Indeed, stress reduction interventions, which have been shown to be effective for alleviating caregivers' psychological distress, have also been linked with adaptive changes in executive function and other cognitive indices (Lavretsky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these findings might inform the development and delivery of interventions that aim to improve the cognitive well being of caregivers through targeting the psychological sequelae associated with the caregiving experience. Indeed, stress reduction interventions, which have been shown to be effective for alleviating caregivers' psychological distress, have also been linked with adaptive changes in executive function and other cognitive indices (Lavretsky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies have been shown to be effective for reducing stress reactivity and anxiety [36,38,39] as well as depression [38,40], and can improve comfort levels and well-being measures in individuals with medical illnesses [41]. Mindfulness is strongly linked with reduced negative affect [42] and can reduce anger and aggression [43].…”
Section: Improved Outlook Pain Reliefmentioning
confidence: 99%
“…More recently, 3 small trails of meditation intervention studies measured telomerase activity in healthy volunteers, 25 individuals with obesity, 26 and caregivers of patients with Alzheimer disease. 27 One study also measured TL in healthy meditators. 28 Although each of these trials demonstrated promising results, they had small sample sizes (ranging from 37-60 participants) and only postassessment measurements, 25 and the one study that measured TL (as opposed to telomerase) 28 lacked randomization.…”
Section: Introductionmentioning
confidence: 99%